Pathological changes by spirorchiid eggs in hawksbill sea turtle (Eretmochelys imbricata) stranded off brazilian coast - SILVA,MARIA APARECIDA DA (2022)
Abstract Eretmochelys imbricata (hawksbill turtle) is classified as a critically endangered species at world level; in Brazil, it is listed among the threatened species. Spirorchiids are parasites of the circulatory system of chelonians which may cause serious lesions in the various tissues of the host due to deposition of eggs in the bloodstream. In this context, the aim of the present study was to describe the pathology caused by spirorchiid eggs in E. imbricata from the Brazilian over a five year period. A total of 29 animals were analyzed, of which nine (31%) presented lesions associated to spirorchiids eggs. The lesions were: granulomatous enteritis in six (66.66%), granulomatous splenitis in five (55.55%), granulomatous hepatitis in three (33.33%), granulomatous pneumonia in three (33.33%), granulomatous pancreatitis in two (22.22%), and granulomatous adrenalitis in one specimen (11.11%). Concluded the main lesion in Eretmochelys imbricata was giant-cell granulomatous inflammatory reaction to the parasite’s eggs. Animals exhibiting poor physical health were more susceptible to presenting such lesions.